2009
DOI: 10.1089/acm.2008.0436
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Randomized Controlled Trials on DanShen in the Treatment of Ischemic Vascular Disease

Abstract: The quality of DanShen RCTs in mainland China has not been improved significantly over recent years, and the overall quality of DanShen RCTs is still poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The quality of the RCTs is a major issue. Previous sampled surveys [86][87][88][89][90] on the RCTs on traditional Chinese medicine conducted in China showed poor quality of RCT conduct and reporting. This systematic review found that most of retrieved RCTs are of low to medium quality.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the RCTs is a major issue. Previous sampled surveys [86][87][88][89][90] on the RCTs on traditional Chinese medicine conducted in China showed poor quality of RCT conduct and reporting. This systematic review found that most of retrieved RCTs are of low to medium quality.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have shown that tanshinone IIA and its sodium sulfonate have a wide spectrum of pharmacological activities, including cardioprotective, neuro-protective, anticancer, immuno-modulating, anti-osteoporotic, cytotoxic and apoptosis-inducing, anti-atherosclerotic, and anti-oxidative and radicalscavenging effects. However, although there have been 150 randomized clinical trials for danshen in the treatment of ischemic vascular diseases which are all conducted in mainland China, only 6.7% (10/150) of these studies are considered with high quality (Jadad score 4) [81]. A recent Cochrane systematic review claimed that the evidence to support use of danshen preparations is too weak to make any judgement about its clinical efficacy [82].…”
Section: Salvia Miltiorrhiza (Danshen)mentioning
confidence: 99%
“…However, the methodological quality of many studies has been criticized. 110 A 2010 Cochrane Review of traditional Chinese herbal products for stable angina identified 242 potentially relevant publications, which were reduced to 127 RCTs. 108 Of these, only three finally met the inclusion criteria, but even these suffered from methodological flaws.…”
Section: Clinical Evidence Of Chm's Efficacy In Treating Anginamentioning
confidence: 99%